Analisis Akuntabilitas Laporan Keuangan Pada SMP Swasta Nasrani Belawan - Marviana, Ratna Dina; Lumban Tobing, Fany Farida (UNIVERSITAS DHARMAWANGSA, 2023)
Non-profit organization (school) financial reports prepared based on PSAK No. 45 provides information about the resources provided by the resource provider and can also be used as a consideration for decision making. If a non-profit organization does not present financial reports that comply with standards, it will reduce the trust of resource providers in providing resources to a non-profit organization. The purpose of this research is to find out whether the financial reports presented by the Belawan Christian Private Middle School show accountability and transparency as well as planning and administration in accordance with PSAK No. 45. The type of data used in this research is qualitative data which describes a brief history, organizational structure, vision and mission. This research uses secondary and primary data sources, namely data obtained from the field and other sources. The data collection methods used in this research are documentation and interviews. The data analysis technique used in this research is a descriptive method, which is done by interpreting the data obtained so as to provide an overview of the problems faced. The results of this research indicate that the financial reports at the Belawan Christian Private Middle School cannot reflect accountability and transparency in accordance with PSAK No. 45, In presenting financial reports, the Belawan Christian Private Middle School presents monthly financial reports and there are no annual financial reports, resulting in inadequate information. Based on PSAK No. 45 regulations, non-profit entity financial reports should be presented annually, financial reports in accordance with PSAK No. 45. 45, namely Financial Position Report, Activity Report, Cash Flow Report, and Notes to Financial Reports.Keyword: Akuntability, Financial Report, Junior High School, Christian, Belawan